WORD-ATTACK SKILLS FOR INDONESIAN LEARNERS - Joko Pranowo (TEFLIN, 2006)
The typical drawbacks that affect most Indonesian learners studying English as the target language concern the strategies in dealing with new dictions. The rule of thumb is that the learners are usually tempted to directly look up the meaning in a dictionary when other ways such as guessing the meaning from the context or by dissecting the words into smaller units so that they are able to get a hint from the base word cannot be engineered. As a result of this activity then, they miss crucial points in the realm of word enrichment. This article will shed some light on how to deal with new words and claim that it is not the meaning of a new word that should be the first priority.